ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KETAHANAN PANGAN RUMAH TANGGA PETANI (STUDI KASUS : DESA TIMBULHARJO, SEWON, BANTUL) - Vizia Lukri Damayanti (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to determine the factors that affect food security of farm households in Timbulharjo Village, Sewon, Bantul. Factors used in this study were income, head of family education, age of head of household, marital status, number of family members and ownership of savings account. This study uses primary data obtained from direct interviews by asking a list of questions. The analytical technique used was logistic regression analysis, then completed by using the maximum likelihood method which included Nagelkerke R Square equivalent to coefficient of determination (R2), significance test Simultaneously (Overall Model Test) is equivalent to F test in linear regression, Wald test is equivalent to t test on OLS. The income and education of the head of the household have a positive effect on food security, while the number of family members has a negative effect on food security. Based on the partial test, the income variable, the education of the head of the household, the number of family members affect the food security, while the age of the head of the family, marital status, and savings ownership have no effect on food security.